Molecular characterization of equine infectious anaemia virus strains detected in England in 2010 and 2012. Issue 6 (7th August 2019) - Dorey‐Robinson, Daniel L. W.; Locker, Nicolas; Steinbach, Falko; Choudhury, Bhudipa
Abstract: Equine infectious anaemia virus (EIAV) is a retrovirus with worldwide distribution which is notifiable to the OIE. Despite its importance to the equine industry, most information regarding its biology have been obtained using only two strains (EIAVWYO and EIAVLIA ) from the USA and China, respectively. Recently full genome sequences from Ireland, Italy and Japan have been published; however, this is still not representative of the number of EIAV outbreaks experienced globally each year. The limited availability of published sequences makes design of a universal EIAV PCR difficult, hence diagnosis is solely reliant on serology. Accordingly, it is important to further investigate the re‐emerging cases in other areas of the world. Here, we provide information regarding the outbreaks of EIA in England in 2010 and 2012 including the molecular characterization of strains. Full genome was obtained for two symptomatic cases but could not be resolved for the asymptomatic cases. The two British genomes from 2010 (EIAVDEV ) and 2012 (EIAVCOR ) each represent a new phylogenetic group, each differing genetically from the other available full genome sequences by 21.1%–25.5%. That the majority of new EIAV full genome sequences to be published adds another phylogenetic group indicates that the surface of EIAV global diversity is just being scratched. These data highlight that further work is needed to fully understand EIAV genetic diversity, namely the full genome sequencing of EIAV cases from a variety of locations and time points. This would aid both the use of phylogenetics in parallel with horse tracing as the epidemiological tool of disease tracking and the design of a universally applicable molecular diagnostic method.